PERAN ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DI RUMAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SD NEGERI 1 SIDORENGGO AMPELGADING - Yurindhar Rizcha Utama Lya; Muchammad Hanief; Mutiara Sari Dewi (VICRATINA, 2020)
Interest is a very important thing in an education, with the interest of children will be very easy to accept new things even to explore things that were previously known. In this study the researchers focus on the problem of the role of parents in fostering children's interest in learning when the learning process is carried out at home. Likewise with the interests of children and some of the supporting and inhibiting factors that exist in this problem. This research was conducted to parents in the village of Sidorenggo Ampelgading Malang whose children and children carry out their education at SD Negeri 1 Sidorenggo Ampelgading Malang. The method used in this research is descriptive qualitative research method with data collection techniques using observation, interviews and field notes. In this study the researchers concluded that the role of parents in children's learning interests is very large, especially if the learning process is done at home. Parents who help the school in delivering subject matter and doing daily assignments and examinations have a role as a motivator for children to not be lazy, so that achievement will continue to grow and increase.